Novel GO/silica composite aerogels with enhanced mechanical and thermal insulation properties prepared at ambient pressure. (19th May 2018) - Hong-li, Liu; Xiang, He; Hong-yan, Li; Jing, Li; Ya-jing, Li
ABSTRACT: Novel graphene oxide (GO)/silica composite aerogels were fabricated to strengthen the nanostructure and overcome inherent fragility of silica aerogels by a sol-gel method using tetraethyl orthosilicate (TEOS) and low concentration of graphene oxide solution as the main materials, followed by an environmentally friendly ambient pressure drying (APD). The interaction between GO nanosheets and silica matrix was investigated by using FTIR and SEM. Meanwhile, the mechanical properties and thermal conductivity of aerogels were also studied. The results showed that GO were uniformly dispersed in the silica aerogel, and there is a good physico-chemical combination between GO and silica matrix. The addition of GO can enhance the mechanical of the composite aerogels, and when the GO content is increased from 0 to 3wt%, the mechanical strength is improved from 0.04 MPa to 0.65 MPa. Meanwhile, the thermal conductivity of composite aerogels first decreases and then increases with increasing GO content, and the optimal value is 0.018 W/m K. The composites with outstanding properties prepared by APD are potential for insulation applications.